Synthesis, Antiproliferative and Antimalarial Activities of Dinuclear Silver(I) Complexes with Triphenylphosphine and Thiosemicarbazones Ligands - Nur Adila Fatin Mohd Khir; Mohd Ridzuan Mohd Abdul Razak; Fariza Juliana Nordin; Nur Rahimah Fitrah Mohd Sofyan; Nur Fadilah Rajab; Rozie Sarip (Indonesian Journal of Chemistry, 2021)
A series of six sulfur-bridged dinuclear silver(I) thiosemicarbazone complexes were synthesized through the reaction of silver(I) nitrate with 4-phenyl-3-thiosemicarbazone derivatives together with triphenylphosphine (PPh3) (in a 1:1:2 molar ratio). Following structural characterizations using various techniques such as elemental analysis, Fourier-transform infrared (FTIR) spectroscopy, as well as 1H, 13C, 31P{1H}s, COSY, and 1H-13C nuclear magnetic resonance (NMR) spectroscopy, it was found that the thiosemicarbazone ligand exists in the form of a thione rather than thiol tautomer. Subsequently, MDA-MB-231 and MCF-7 breast cancer cell lines, as well as the HT-29 colon cancer cell lines, were used to investigate the in vitro antiproliferative activities of these complexes. In all cases, the IC50 values were in the potent micromolar range. Besides, the aforementioned complexes also had good antiplasmodial activity against chloroquine-resistant P. falciparum, as per the results of histidine-rich protein 2 (HRP2) assays and cytotoxicity evaluations of MDBK cells.